The idea of Pakistan - Cohen, Stephen P., 1936- (Washington, D.C. : Brookings Institution Press, 2004)
"In recent years Pakistan has emerged as a strategic player on the world stage - both as a potential rogue state armed with nuclear weapons and as an American ally in the war against terrorism. But our understanding of this country is superficial." "To probe beyond the headlines, Stephen Cohen, author of the prize-winning India: Emerging Power, offers a panoramic portrait of this complex country - from its origins as a homeland for Indian Muslims to a military-dominated state that has experienced uneven economic growth, political chaos, sectarian violence, and several nuclear crises with its much larger neighbor, India."--BOOK JACKET.
1. The idea of Pakistan -- 2. The state of Pakistan -- 3. The army's Pakistan -- 4. Political Pakistan -- 5. Islamic Pakistan -- 6. Regionalism and separatism -- 7. Demographic, educational, and economic prospects -- 8. Pakistan's futures -- 9. American options.
Includes bibliographical references (p. 329-367) and index.
Keywords: Pakistan